2014
DOI: 10.2967/jnumed.113.132712
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of 18F-MNI698: An 18F-Labeled Radiotracer for Imaging of Serotonin 4 Receptors in Brain

Abstract: Serotonin 4 receptors (5-hydroxytryptamine receptor 4 [5HT4R]) hold promise as a novel therapeutic approach to multiple brain disorders, including Alzheimer and Huntington disease. In vivo imaging of these receptors with selective 5HT4R radiotracers and PET would be valuable to investigate alterations in 5HT4R in different brain disorders and to assist drug discovery. In this study, 18 F-MNI698 was evaluated as a potential PET radiotracer for imaging of 5HT4R in the brain. Methods: Eighteen PET studies were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Compared to similar reproducibility studies published for other PET tracers of the serotoninergic system in primates (Chen et al, 2012; Tavares et al, 2014), the reproducibility parameters of [ 18 F]2FNQ1P binding potential showed more satisfactory results. In consequence, the ability to detect changes in 5-HT 6 R availability or occupancy in in vivo studies, would be more sensitive with [ 18 F]2FNQ1P, giving a supplemental chance of elucidating functional and dysfunctional serotonin transmission in the brain and facilitating the development of therapeutic drugs targeting 5-HT 6 Rs.…”
Section: Discussionsupporting
confidence: 48%
“…Compared to similar reproducibility studies published for other PET tracers of the serotoninergic system in primates (Chen et al, 2012; Tavares et al, 2014), the reproducibility parameters of [ 18 F]2FNQ1P binding potential showed more satisfactory results. In consequence, the ability to detect changes in 5-HT 6 R availability or occupancy in in vivo studies, would be more sensitive with [ 18 F]2FNQ1P, giving a supplemental chance of elucidating functional and dysfunctional serotonin transmission in the brain and facilitating the development of therapeutic drugs targeting 5-HT 6 Rs.…”
Section: Discussionsupporting
confidence: 48%
“…4). Furthermore, the A 2A R occupancy at caffeine doses of 2.5, 5, and 10 mg/kg became 70%, 72%, and 81%, respectively, after correction for self-occupancy (16,20). Regardless of possible nonnegligible receptor occupancy by preladenant, our study demonstrated that 11 C-preladenant has suitable binding properties and pharmacokinetic profile, which warrants its translation to human studies.…”
Section: Discussionmentioning
confidence: 59%
“…However, the question is whether adrenal glands may actually be viewable through this approach. In this regards, radiolabeled 5-HT4R ligands have successively been used for positron emission tomography (PET) scan imaging in monkeys and humans [95,96]. Interestingly, monkey adrenals have been well visualized in whole-body PET images [97] but such observations are still lacking in man.…”
Section: Perspectivesmentioning
confidence: 99%